Discurso e arquivística: uma análise da enunciação do termo pós-custodial no contexto português e brasileiro - SILVA, Amanda Marissa Soares da (2017)
The term post-custodial appears in a contemporary and Archival Science perspective appears as an assumed paradigm shift of archival science custodial to archival science post-custodial. So, in this research through the theoretical framework of methodological Discourse Analysis of french instrumentaliza the array analysis of texts, studied the enunciation and discursively speech related to post-custodial in Portuguese and Brazilian context. Archival Science from your home, always been attached and influenced other disciplines within his directing techniques and methods to changes in their theoretical approaches. The change of the document object to the archival information is one of the recurring enunciations in post-custodial scenario. Thus, use of the term post-custodial by certain authors States in archival science apparently, a change of terrain (theoretical/practical). Through this questioning analyzed three important theoretical texts in the tradition, they are: Armando Malheiro da Silva (2009; 2015), Fernanda Ribeiro (2005; 2011) and Maria Odila Fonseca (2005). This analysis seeks to understand through discourse analysis as is and the enunciations related to post-custodial within the scientific production in the area and to what extent such meaning effectively presented as a change of terrain. Finally, builded a comparison chart between the authors, their statements and discursive formations that link when in the treatment of the concept/term post-custodial, coming to a fundamental conceptual discourse panorama at the current stage of the scientific area.